Impact of COVID-19 pandemic on key performance indicators in pancreatobiliary endoscopy: prioritise, minimise risk, keep scoping and training. Issue 4 (15th December 2020) - Esmaily, Shiran; Yau, Chia Chuin; Dwarakanath, Deepak; Hancock, John; Mitra, Vikramjit
Abstract : Background: The COVID-19 pandemic has profoundly affected endoscopy services including pancreatobiliary (PB) endoscopy across the UK. The British Society of Gastroenterology and Joint Advisory Group have issued guidance for managing endoscopy services safely throughout this period. There have been perceived concerns among the PB endoscopists that wearing full personal protective equipment might have an adverse impact on key performance indicators (KPIs) in endoscopic retrograde cholangiopancreatography (ERCP) and endoscopic ultrasound (EUS) procedures leading to non-compliance with the national guidelines. The aim of the study was to assess the impact of COVID-19 pandemic on KPIs in ERCP and EUS and ascertain the risk of procedure-related complications. Methods: A retrospective audit of a prospectively maintained endoscopy database was carried out between 18 March and 31 July 2020. Results: 146 ERCP procedures (common bile duct (CBD) cannulation rate of naïve papilla 89.2%, complete CBD stone extraction rate at first ERCP 88.2%, biliary stricture decompression rate 91%) and 87 EUS procedures (diagnostic accuracy of EUS-fine needle aspiration 92%) were carried out during this period. ERCP-related complications included pancreatitis (4.8%), bleeding (0.68%) and cholangitis (0.68%). 30-day ERCP procedure-related mortality was 0.68%. There were no complications or procedure-related mortality in the EUS group. Conclusion: This is the first study looking at the impact of COVID-19 on KPIs and procedure-related complications in ERCP and EUS in the literature. Our study confirms that a high-quality PB endoscopy service can be delivered safely and effectively during the COVID-19 pandemic.